How Costly Are Debt Crises? - Furceri, Davide (IMF Working Papers; Working Paper, 2011)
The aim of this paper is to assess the short- and medium-term impact of debt crises on GDP. Using an unbalanced panel of 154 countries from 1970 to 2008, the paper shows that debt crises produce significant and long-lasting output losses, reducing output by about 10 percent after eight years. The results also suggest that debt crises tend to be more detrimental than banking and currency crises. The significance of the results is robust to different specifications, identification and endogeneity checks, and datasets.